A Relationship Study of Teachers’ Perception towards Professional Development and Their Job Satisfaction in Guilin University of Electronic Technology, Guangxi, China - Wu, Xueying; Ye, Yan (Scholar: Human Sciences, 2017)
The main purpose of this study was to determine the relationship between teachers’ perception towards professional development and their job satisfaction in GuiLin University of Electronic Technology, GuangXi, China in the academic year 2014 – 2015.A total of one hundred and forty – one (141) full – time teachers from the GuiLin University of Electronic Technology were surveyed for this study. The main resource of data was the questionnaire that investigated the teachers’ perception towards professional development and their job satisfaction. The collected data were analyzed by using the mean, standard deviation and Pearson Product Moment Correlation Coefficient. The research findings indicated that the level of teachers’ professional development was the high in the school, and from the results of teachers’ job satisfaction, it was found that the level of their job satisfaction was regarded as ‘moderate’. A moderate possitive relationship between teachers’ perception towards professional development and their job satisfaction was existing in GuiLin University of Electronic Technology, GuangXi province of China.